The evaluation of spontaneous space closure after the extraction of first permanent molars - Teo, T. K. Y.; Ashley, P. F.; Parekh, S.; Noar, J. (European archives of paediatric dentistry, 2013)
Aim In the UK, first permanent molars (FPMs) of poor prognosis are often planned for extraction so that second permanent molars (SPMs) erupt favourably to replace the FPMs. However, there is little published data to support this treatment strategy. The aim of this study was to assess the success of planned FPM extractions conducted 5 years ago at a dental hospital in London. Methods Two hundred and thirty-six SPMs from 63 patients were clinically assessed. The position of each SPM was recorded in relation to the second premolar, against patient Angle’s classification and SPM radiographic development stage at the time of FPM extraction. Statistics Results were analysed using ordered logistic regression. Results At the time of FPM extraction, only 54 % of SPMs were at the “ideal” stage of development (Demirjian’s dental development stage E). Upper and lower arches yielded significantly different results with 92 % of all upper extractions resulting in complete space closure regardless of SPM development stage. Only 66 % of lower FPMs extracted at SPM stage E had complete space closure and no significant relationship was found between lower SPM development stage and its subsequent space closure. Space closure in both arches also appeared independent of patient Angle’s classification. Conclusions Although only over half the patients had FPMs extracted at the “ideal time”, this did not appear to influence successful positioning of the upper or lower SPM. More research is required to investigate and confirm which predictive parameters have a significant effect on post-extraction orthodontic development, especially in the lower arch.